Studi Komparatif Terhadap Pandangan HKBP Lae Rias Nauli Dan GKII Lae Rias Tentang Adat Pernikahan Masyarakat Batak Toba Di Desa Lae Rias Kecamatan Sumbul - Pitta Sri Hartati Sihotang; Bestian Simangunsong; Megawati Manullang; Erman S. Saragih; Tiffany Tamba (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
The differences in views between HKBP and GKII regarding Toba Batak wedding customs reflect a large debate in Lae Rias village, Sumbul District, Dairi Regency. This debate has made the people in Lae Rias less caring and less tolerant. The aim of this research is to examine the differences in views between HKBP Lae Rias Nauli and GKII Lae Rias regarding the marriage customs of the Toba Batak community in Lae Rias village, Sumbul District. This research uses a descriptive qualitative approach method by conducting interviews with pastors, congregations living in HKBP Lae Rias Nauli and GKII Lae Rias. The data was analyzed to identify differences in views in their understanding of Toba Batak marriage customs. The research results showed that HKBP Lae Rias Nauli tended to maintain Toba Batak marriage customs. Meanwhile, GKII Lae Rias places greater emphasis on marriage without involving Toba Batak customs. There is a need for deeper dialogue between HKBP and GKII and the entire Toba Batak community in Lae Rias Village to achieve a better understanding of the role of custom in Christianity. It is also important to provide new knowledge to the younger generation about culture so that they can maintain and appreciate it because if understood properly and correctly, religion and culture complement each other.